The white-footed mouse - Lange, Willem, 1935- (Bunker Hill Pub., 2012)
An eight-year-old boy's father teaches his son an outdoorsman's lessons about wildlife, canoing, and handling a gun. When the boy is allowed to accompany his father to hunting camp, where they discover a shivering mouse who shares the warmth of their stove, the boy reminds his dad of a lesson he was taught.